2021
DOI: 10.3390/polym13121935
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Remendable Polyurethane Network Cross-Linked via Reversible Diels–Alder Reaction

Abstract: We prepared a series of thermally remendable and recyclable polyurethanes crosslinked via reversible furan-maleimide Diels–Alder reaction based on TDI end-caped branched Voranol 3138 terminated with difurfurylamine and 4,4′-bis(maleimido)diphenylmethane (BMI). We showed that Young modulus strongly depends on BMI content (from 8 to 250 MPa) that allows us to obtain materials of different elasticity as simple as varying BMI content. The ability of DA and retro-DA reactions between furan and maleimide to reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The latter change of volume is also associated with a change in the geometry of the individual cells. Simultaneously, the change in the viscoelastic and viscoplastic properties of the PU matrix should be assumed due to the PU matrix cross-linking [ 27 ], and partial hydrolysis [ 28 ]. As a complex material response, the varying degrees of swelling of the PU cell walls material were proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The latter change of volume is also associated with a change in the geometry of the individual cells. Simultaneously, the change in the viscoelastic and viscoplastic properties of the PU matrix should be assumed due to the PU matrix cross-linking [ 27 ], and partial hydrolysis [ 28 ]. As a complex material response, the varying degrees of swelling of the PU cell walls material were proposed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zheng et al prepared self-healable PU composites based on furan–maleimide DA chemistry by incorporating tetramethylene tetranitramine (HMX) filler to improve the tensile strength (σ) up to 13.47 MPa. Similarly, Polezhaev et al reported a triarm thermally remendable and recyclable PU that exhibited σ up to 26 MPa via DA reaction. Yang et al prepared phase-change composites using the maleimide-terminated PEG-based PU and furan-modified dopamine to endow the significant self-healing and photothermal conversion abilities for energy storage applications.…”
Section: Introductionmentioning
confidence: 92%
“…Several approaches were used for the synthesis of CANs using fmDA reaction. The synthesis of highly reprocessable cross-linked polymers may be carried out using monomolecular substrates containing three or more furanic and/or maleimide functional groups [99][100][101]. Depending on the structure and ratio of the monomers, polycondensation by fmDA reaction can lead to branched or cross-linked polymers [102].…”
Section: Synthesis Of Cross-linked Dynamers Using the Fmda "Click" Reactionmentioning
confidence: 99%